89 Longterm follow-up of myotonic dystrophy type 1 patients with pacemaker and implantable cardioverter-defibrillators: a single uk specialist centre experience. (6th June 2022) - zheng, yuran; Glover, Oliver; Walker, Rachel; Somani, Shaheen; Watson, Oliver; Wheeldon, Nigel; Lewis, Nigel
Abstract : Introduction: Cardiac conduction disease and sudden cardiac death is known to be associated with Myotonic Dystrophy type 1 (MD). Patients often require device implantation to prevent sudden cardiac death. Practice for cardiac implantation can be varied throughout national and international centres. ObjectiveTo define the rate and type of device implantation, rate of pacing and outcome in MD patients managed in a single specialist centre.MethodRetrospective analysis of pacing and outcome data on consecutive MD patients managed at Specialist Centre in the UK between 2011 and 2021. Data was retrospectively analysed using electronic patient notes, including pacemaker follow-up reports. Results24/119 MD patients were implanted with a cardiac device. Male:Female 13:11. At implant, patients had a mean age of 56 (95% CI 52 to 59), mean PR interval 217 ms (95% CI 203 to 230), mean QRSd 123 ms (95% CI 109 to 137). Devices implanted included 16 DDDR, 4 CRT-D, 1 CRT-P, 1- ICD and 2 VVI pacemakers. In the Cardiac devices vs Non- cardiac device group 10/24 (43%) vs 12/95 (13%) died, P=0.001. Mean survival from time of implant to death was 62 months (95% CI 19 to 104). 7 (88%) patients who died in the devices group had evidence of progressive conduction disease prior to death, indicated by progressive increases in mainly atrial pacing. No sudden cardiac deaths were recorded during follow up. 1 ventricular Tachycardia treated by ICD therapy. Conclusion: In our cohort of myotonic dystrophy patients 20% required device implantation. Pacing indication remains varied. Mean survival post device implantation is high. Despite sudden cardiac death being prevented through appropriate cardiac device implantation, the risk of mortality remains high in patients with myotonic dystrophy and conduction disease. A multidisciplinary approach is required to provide the best outcome for these patients. Conflict of Interest: none